English English - Yumahendra, Zefly; Maftuh, Bunyamin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
The main element in an individual's personality development is education. This research uses a non-statistical qualitative field method to identify Merdeka Belajar Curriculum Development Strategy as an Effort to Improve the Quality of Education in SDN 01 Sukaresmi The research findings are as follows: (1) curriculum planning that integrates all school structures, (2) In SDN 01 Sukaresmi, the curriculum vice principal assists the school principal in coordinating the implementation of the Merdeka Belajar Curriculum. The curriculum vice principal then helps the school principal in coordinating the teachers, (3) Merdeka Belajar has been implemented in SDN 01 Sukaresmi since 2023. The Merdeka Belajar Curriculum was subsequently enforced with regulations from the Minister of Education, and selected schools in SDN 01 Sukaresmi adopted it.